2017
DOI: 10.4236/ojped.2017.73024
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitudes and Practices of Parents in the Vaso-Occlusive Crises of the Sick Children in Brazzaville

Abstract: Objectives: to evaluate the parents' knowledge of vaso-occlusive crises, to identify their attitudes and practices. Method: a retrospective, transversal, descriptive and analytical study carried out between January and June 2016 at the HUC of Brazzaville. The parents of sickle cell children aged 2 to 17 years, followed for at least one year, were interviewed. Results: a total of 319 parents were interviewed, including 221 women (69.3%) and 98 men (30.7%) with a mean age of 40.8 ± 9 years. They were unschooled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 8 publications
0
1
0
Order By: Relevance
“…Most of the parents had some level of education, with more than 28.8% having a bachelor's and above education. In another study, 20% of the parents were uneducated [20].…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…Most of the parents had some level of education, with more than 28.8% having a bachelor's and above education. In another study, 20% of the parents were uneducated [20].…”
Section: Discussionmentioning
confidence: 91%
“…Most of the parents had some level of education, with more than 28.8% having a bachelor's and above education. In another study, 20% of the parents were uneducated [ 20 ]. Education level has been reported to have an impact on the attitude of the parents towards their child’s disease [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Also, this was in agreement with Yadav, (2017) who reported that after providing education post test scores of knowledge improved significantly (100%). Similarly, in study conducted by Okoko et al, (2017) who indicated that knowledge of the sickle cell disease in Brazzaville is poor for 66.6% of parents.This was disagreement with Nakazwe and Siziya, (2017) who reported that respondents had average knowledge about sickle cell and factors that precipitate crises(53.9 %).…”
Section: Discussionmentioning
confidence: 93%